Child-Friendly Justice – Polish Perspective - Lis, Wojciech (Child-Friendly Justice. The Participation and the Rights of the Child in Court Proceedings From a Central European Comparative Perspective, 2025)
Abstract:A child has the right to express his/her opinion, especially in matters concerning him/her and those that concern his/her legal interest, especially in the course of court proceedings. The child’s right to express himself/herself during court proceedings is a manifestation of the child’s appreciation as a valuable source of information. Hearing the child increases the chances of determining the factual circumstances of the case as fully as possible and, consequently, makes it easier to issue an accurate decision. Properly conducted, it allows in almost every case to determine the child’s current care and upbringing situation as well as his/her relationship with his/her parents. It allows one to learn about the child’s preferences and expectations regarding the court’s decision. Creating conditions for the child to exercise the right to express himself/herself during a hearing is a manifestation of recognising the child’s subjectivity, treating him/her as capable of understanding the situation that is the subject of the proceedings and expressing his/her position. Giving the child a chance to express his/her needs allows them to be diagnosed and taken into account when making a decision, which should always be aimed at realising the child’s good whenever a child appears. Keywords: freedom of expression, rights of the child, welfare of the child, court proceedings, grounds for hearing